Respostas

2014-06-03T09:56:13-03:00
A-)4x²-9x=0  a=4 b=(-9) c=0
delta = b²-4ac
(-9)²-4(4).(0)
81

bhaskara 
-b+/-raiz de delta/2.a

-(-9)+/- raiz de 81/2.4
9+/-9/8
x'= 9+9/4 = 18/4 = 4,5

x'' = 9-9/4 = 0/4 = 0   S={4,5)

B-)3x²+5x=0   a=3 b=5 c=0
5²-4.(3).(0)
25

x=-b+/-raiz de delta/2.a
x=-5+/- 5/6
x'=5+5/6 = 10/6 = 1,66
x'' = 5-5/6 = 0/6 = 0
S={1,66}

C-)4x²-12x=0    a=4 b=(-12) c=0
(-12)²-4.(4).(0)
144

x=-b+/-raiz de delta/2.a
x=-(-12)+/- 12/2.4
x=12+/-12/8
x'=12+12/8 = 24/8 = 3
x''= 12-12/8 = 0/8= 0
S={3}

D-)5x²-x=0  a=5 b=(-1)
(-1)²-4.(5).(0)
1
X= -b+/-raiz de delta/2.a
x= -(-1)+/-1/2.5
x=1+/- 1 /10
x' = 1+1/10 = 2/10 = 0,2
x'' = 1-1/10 = 0/10 = 0
S={0,2}